Scratch-resistant PE composite board and preparation method thereof
By introducing anti-scratch strengtheners into the PE plastic sealing layer to form a strong protective layer, the problem of insufficient scratch resistance of PE composite panels is solved, and the scratch resistance is improved while maintaining optical aesthetics.
Patent Information
- Application Number
- CN202510912106.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-09-05
- Estimated Expiration
- 2045-07-03
AI Technical Summary
The PE layer of existing PE composite sheets has insufficient scratch resistance. Slight scratches lead to decreased light transmittance and weakened protective performance. Existing technologies cannot effectively coordinate the contradiction between migration control and interface strengthening.
An anti-scratch enhancer is introduced into the PE plastic sealing layer. A chain compound is formed through the reaction of dimethyl fluoromalonate, diethylenetriamine and n-butylamine. Combined with the side chain branching of tributylchlorosilane, a strong protective layer is formed to optimize the balance between friction performance and scratch resistance.
The surface scratch resistance of PE composite sheets is significantly improved, while maintaining optical aesthetics. The anti-scratch strengthener forms a low-friction, high-strength layer on the surface, hindering the penetration and expansion of scratches and enhancing protective performance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer composite plates, and in particular relates to a scratch-resistant PE composite plate and a preparation method thereof. Background Art
[0002] PE-based composite panels (including wood-plastic and aluminum-plastic), leveraging the weather resistance, processability, and optical transparency of polyethylene (PE), are widely used in architectural decoration, furniture, and packaging. In wood-plastic panels, the wood substrate is composited with PE, retaining the wood appearance while improving moisture and corrosion resistance. Aluminum-plastic panels, on the other hand, are bonded to the metal substrate via a PE layer, preserving the metallic luster while balancing lightweightness with surface smoothness. However, the PE layer, as a surface protective layer, lacks scratch resistance, a key shortcoming of the composite panels. Even minor scratches can increase surface light scattering, resulting in reduced light transmittance and affecting decorative properties. Scratches act as stress concentration points, accelerating fatigue cracking in the PE layer and compromising protective performance.
[0003] To improve the scratch resistance of PE composite sheets, existing technologies primarily employ the following solutions: 1. Adding inorganic fillers (such as calcium carbonate and silica) to increase surface hardness. However, the introduction of these fillers increases scattering in the PE protective layer, affecting the aesthetics of the sheet. Furthermore, the fillers hinder the slippage of the PE molecular chains, deteriorating the impact resistance of the protective layer. 2. Using a silicone / fluoride blend to reduce friction, leveraging its low surface energy to concentrate on the surface of the PE protective layer, lowering the surface friction coefficient and minimizing scratches. However, these fillers form a loose physical accumulation layer on the surface, unable to resist puncture stress or inhibit scratch propagation, resulting in a minimal improvement in scratch resistance. Existing technologies are unable to reconcile the contradiction between migration control and interface strengthening, hindering improvements in the scratch resistance of PE protective composite sheets. Summary of the Invention
[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a scratch-resistant PE composite board and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A scratch-resistant PE composite board consists of a substrate and a PE plastic sealing layer, wherein the specific components of the PE plastic sealing layer are: 18-25wt% of HDPE resin, 7.5-11wt% of anti-scratch strengthener, 1.9-2.6wt% of compatibilizer, 1.2-1.5wt% of lubricant and 0.1-0.13wt% of antioxidant, and the balance is LLDPE resin.
[0007] The anti-scratch strengthener is prepared by the following method:
[0008] Step A1: Dimethyl fluoromalonate, diethylenetriamine, and anhydrous toluene are premixed, and dry nitrogen is introduced. Trimethylaluminum is added and mixed thoroughly. The mixture is heated to 80-100°C and stirred under reflux for 3-4 hours. Then, n-butylamine is added and the reaction is continued for 0.5-0.7 hours. After completion of the reaction, the toluene is removed by rotary evaporation to obtain Intermediate 1.
[0009] In the reaction of step A1, the amount ratio of dimethyl fluoromalonate, diethylenetriamine, n-butylamine, trimethylaluminum and anhydrous toluene is 0.1 mol: 0.1 mol: 40-60 mmol: 0.1-0.18 g: 85-100 mL. Under the promotion of trimethylaluminum, dimethyl fluoromalonate and diethylenetriamine undergo amine transesterification to form a chain compound which is capped with n-butylamine.
[0010] Preferably, the dimethyl fluoromalonate is one of dimethyl 2-fluoromalonate and dimethyl difluoromalonate, and the balance between the friction performance and the anti-scratch performance of the surface can be adjusted by regulating the fluorine content.
[0011] The specific reaction route is as follows:
[0012]
[0013] Step A2: Premix the intermediate 1, 6-bromohexanol, and dimethylformamide, add potassium carbonate, and heat to 60-70°C with stirring for 5.5-7 hours. After the reaction is complete, cool, add deionized water for washing, separate the aqueous phase by centrifugation, and vacuum dry to obtain the intermediate 2.
[0014] In the reaction of step A2, the ratio of intermediate 1, 6-bromohexanol, potassium carbonate, and dimethylformamide is 50 g: 0.14-0.18 mol: 2.5-3.5 g: 120-150 mL. Potassium carbonate is an acid-binding agent to promote the substitution of 6-bromohexanol with the secondary amine in the intermediate 1 molecule. The specific reaction route is as follows:
[0015]
[0016] Step A3: Premix the intermediate 2, triethylamine, and acetone, cool the mixture to a temperature not exceeding 10°C, introduce dry nitrogen, slowly add tributylchlorosilane, and stir to react for 1.5-2 hours. Return the mixture to room temperature and continue stirring to react for 3-4 hours. After the reaction is complete, remove the acetone by rotary evaporation, then add saturated sodium bicarbonate solution to wash the mixture, separate the aqueous phase, and vacuum dry to obtain an anti-scratch enhancer.
[0017] In the reaction of step A3, the ratio of the amount of intermediate 2, tributylchlorosilane, triethylamine and acetone is 50g:0.12-0.15mol:15-20mL:180-240mL. Tributylchlorosilane reacts with the hydroxyl group on the side chain of the intermediate 2 molecule to introduce a branched butyl group into the side chain. The specific reaction route is as follows:
[0018]
[0019] Preferably, the compatibilizer is HDPE-g-MAH resin, which improves the compatibility between the components, promotes the performance consistency of the PE plastic sealing layer, and reduces the formation of scratches.
[0020] Preferably, the lubricant is a compound of calcium stearate and erucamide, which synergistically lubricates, improves the surface quality of the PE plastic sealing layer, and reduces the occurrence of scratches.
[0021] A method for preparing a scratch-resistant PE composite board comprises the following steps: uniformly mixing the raw materials of various components, melt-extruding the raw materials onto the surface of a substrate, and then sequentially hot-pressing, heat-treating, and cooling to form a PE plastic sealing layer on the surface of the substrate to obtain the scratch-resistant PE composite board.
[0022] Beneficial effects of the present invention:
[0023] The present invention is based on PE plastic-sealed composite board, and introduces an anti-scratch strengthener into the PE plastic-sealed layer for blending and modification, which spontaneously forms a strong, stable, and matrix-integrated enriched protective layer near the surface of PE, significantly improving the surface scratch resistance. Compared with the existing technology, it has the following advantages: the anti-scratch strengthener is an organic macromolecular compound, which has little effect on the optical aesthetics of the PE matrix and retains the original appearance of the composite board as much as possible; its molecular main chain is a polyamide structure, which has high rigidity and resistance to plastic deformation, far superior to flexible silicone chains or isolated small fluorocarbon molecules. The fluorine structure introduced in the main chain provides a driving force, prompting its main chain to migrate to the air interface, thereby forming a low-friction, high-strength scratch-resistant layer on the surface, hindering the penetration of friction materials; the side chain contains a large number of tributyl groups as the terminal branched structure, which has higher compatibility with the PE matrix, and is more resistant to friction. In the process of surface enrichment, it tends to the PE layer side, which serves as a supporting spacer structure for the main chain, avoiding excessive accumulation of the fluorinated amide main chain, promoting the formation of an orderly gradient distribution of the main chain, and reducing stress concentration during the scratching process. At the same time, the multi-branched butyl chains form entanglements with the PE macromolecular chains, absorbing and dissipating part of the energy through their own deformation and rotation. More importantly, the entanglement points can effectively disperse and transmit the local scratch stress to a larger range of the PE matrix molecular chain network, avoiding excessive concentration of stress at the scratch tip, matching the performance of the main chain, effectively hindering the penetration and expansion of the scratch, and thus achieving excellent scratch resistance. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0025] Example 1, preparation of scratch-resistant PE composite board, the specific implementation process is as follows:
[0026] (1) Synthesis of scratch-resistant PE composite board
[0027] Step A1: Take dimethyl 2-fluoromalonate, diethylenetriamine and anhydrous toluene and premix them, pass dry nitrogen protection, add trimethylaluminum and mix well, heat to 80°C, stir and reflux to react for 3.5 hours, then add n-butylamine and continue to react for 0.6 hours, wherein the amount ratio of dimethyl 2-fluoromalonate, diethylenetriamine, n-butylamine, trimethylaluminum and anhydrous toluene is 0.1 mol: 0.1 mol: 40 mmol: 0.1 g: 85 mL. After the reaction is completed, the toluene is removed by rotary evaporation to obtain intermediate 1.
[0028] Step A2: Premix the intermediate 1, 6-bromohexanol, and dimethylformamide, add potassium carbonate, and heat to 60°C with stirring for 6 hours. The ratio of the intermediate 1, 6-bromohexanol, potassium carbonate, and dimethylformamide is 50 g:0.14 mol:2.5 g:120 mL. After the reaction is completed and cooled, deionized water is added to wash, the aqueous phase is separated by centrifugation, and vacuum dried to obtain intermediate 2.
[0029] Step A3: Pre-mix the intermediate 2, triethylamine, and acetone, cool the mixture in an ice-water bath and control the temperature to be no higher than 10°C, introduce dry nitrogen for protection, slowly add tributylchlorosilane, and stir the mixture for 1.5 hours. Return the mixture to room temperature and continue stirring the mixture for 3.5 hours. The ratio of the intermediate 2, tributylchlorosilane, triethylamine, and acetone is 50 g:0.12 mol:15 mL:180 mL. After the reaction is completed, remove the acetone by rotary evaporation, then add saturated sodium bicarbonate solution for washing, separate the aqueous phase, and vacuum dry to obtain an anti-scratch strengthener.
[0030] (2) Preparation of composite panels
[0031] The following components are taken in percentage by weight: 18wt% HDPE resin, selected from CH2802 resin raw material; 11wt% anti-scratch enhancer, prepared in-house in this embodiment; 1.9wt% compatibilizer, selected from TY-1053H HDPE-g-MAH resin raw material; 1.2wt% lubricant, selected from industrial grade calcium stearate and erucamide in a weight ratio of 2:1; 0.1wt% antioxidant, selected from antioxidant 1010 and antioxidant 168 in an equal weight ratio; the remainder is LLDPE resin, selected from LL103AA resin raw material;
[0032] The above raw materials were mixed in a high-speed mixer, and the mixture was melt-extruded by a twin-screw extruder. The temperature of the plasticizing zone was set at 200°C. The melt was extruded onto the surface of the aluminum substrate through a dividing die head and sent to a roller press. The pressure was controlled at 1.2±0.1MPa for hot pressing and compounding. The mixture was then sent to a tunnel oven and the temperature was controlled at 100°C for homogenization heat treatment for 30 minutes. Finally, the mixture was spray-cooled to form a PE plastic sealing layer on the surface of the aluminum substrate to obtain a scratch-resistant PE composite board.
[0033] Example 2, preparation of scratch-resistant PE composite board, the specific implementation process is as follows:
[0034] (1) Synthesis of scratch-resistant PE composite board
[0035] Step A1: Take dimethyl 2-fluoromalonate, diethylenetriamine and anhydrous toluene and premix them, pass dry nitrogen protection, add trimethylaluminum and mix well, heat to 90°C, stir and reflux to react for 3 hours, then add n-butylamine and continue to react for 0.5 hours, wherein the amount ratio of dimethyl 2-fluoromalonate, diethylenetriamine, n-butylamine, trimethylaluminum and anhydrous toluene is 0.1 mol: 0.1 mol: 45 mmol: 0.13 g: 90 mL. After the reaction is completed, the toluene is removed by rotary evaporation to obtain intermediate 1.
[0036] Step A2: Premix the intermediate 1, 6-bromohexanol, and dimethylformamide, add potassium carbonate, and heat to 65°C, stirring and reacting for 5.5 hours. The ratio of the intermediate 1, 6-bromohexanol, potassium carbonate, and dimethylformamide is 50 g:0.15 mol:2.8 g:120 mL. After the reaction is completed and cooled, deionized water is added to wash, the aqueous phase is centrifuged, and vacuum dried to obtain intermediate 2.
[0037] Step A3: Pre-mix the intermediate 2, triethylamine, and acetone, cool the mixture in an ice-water bath and control the temperature to be no higher than 10°C, introduce dry nitrogen for protection, slowly add tributylchlorosilane, and stir the mixture for 1.7 hours. Return the mixture to room temperature and continue stirring the mixture for 3 hours. The ratio of the intermediate 2, tributylchlorosilane, triethylamine, and acetone is 50 g:0.13 mol:17 mL:200 mL. After the reaction is completed, remove the acetone by rotary evaporation, then add saturated sodium bicarbonate solution for washing, separate the aqueous phase, and vacuum dry to obtain an anti-scratch strengthener.
[0038] (2) Preparation of composite panels
[0039] The following components are taken in percentage by weight: 20wt% HDPE resin, selected from CH2802 resin raw material; 10.2wt% anti-scratch enhancer, prepared in this embodiment; 2.2wt% compatibilizer, selected from TY-1053H HDPE-g-MAH resin raw material; 1.3wt% lubricant, selected from industrial grade calcium stearate and erucamide in a weight ratio of 2:1; 0.11wt% antioxidant, selected from antioxidant 1010 and antioxidant 168 in an equal weight ratio; the remainder is LLDPE resin, selected from LL103AA resin raw material;
[0040] The above raw materials were mixed in a high-speed mixer, and the mixture was melt-extruded by a twin-screw extruder. The temperature of the plasticizing zone was set at 200°C. The melt was extruded onto the surface of the aluminum substrate through a dividing die head and sent to a roller press. The pressure was controlled at 1.2±0.1MPa for hot pressing and compounding. The mixture was then sent to a tunnel oven and the temperature was controlled at 100°C for homogenization heat treatment for 30 minutes. Finally, the mixture was spray-cooled to form a PE plastic sealing layer on the surface of the aluminum substrate to obtain a scratch-resistant PE composite board.
[0041] Example 3, preparation of scratch-resistant PE composite board, the specific implementation process is as follows:
[0042] (1) Synthesis of scratch-resistant PE composite board
[0043] Step A1: Dimethyl difluoromalonate, diethylenetriamine, and anhydrous toluene were pre-mixed, and dry nitrogen was introduced for protection. Trimethylaluminum was added and mixed evenly. The mixture was heated to 100°C and stirred under reflux for 3.5 hours. Then, n-butylamine was added and the reaction was continued for 0.6 hours. The dosage ratio of dimethyl difluoromalonate, diethylenetriamine, n-butylamine, trimethylaluminum, and anhydrous toluene was 0.1 mol: 0.1 mol: 55 mmol: 0.16 g: 100 mL. After the reaction was completed, the toluene was removed by rotary evaporation to obtain intermediate 1.
[0044] Step A2: Premix the intermediate 1, 6-bromohexanol, and dimethylformamide, add potassium carbonate, and heat to 70°C, stirring and reacting for 6.5 hours. The ratio of the intermediate 1, 6-bromohexanol, potassium carbonate, and dimethylformamide is 50 g:0.17 mol:3.2 g:140 mL. After the reaction is completed and cooled, deionized water is added to wash, the aqueous phase is centrifuged, and vacuum dried to obtain intermediate 2.
[0045] Step A3: Pre-mix the intermediate 2, triethylamine, and acetone, cool the mixture in an ice-water bath and control the temperature to be no higher than 10°C, introduce dry nitrogen for protection, slowly add tributylchlorosilane, and stir the mixture for 2 hours. Return the mixture to room temperature and continue stirring the mixture for 3.5 hours. The ratio of the intermediate 2, tributylchlorosilane, triethylamine, and acetone is 50 g:0.15 mol:20 mL:240 mL. After the reaction is completed, remove the acetone by rotary evaporation, add saturated sodium bicarbonate solution for washing, separate the aqueous phase, and vacuum dry to obtain an anti-scratch strengthener.
[0046] (2) Preparation of composite panels
[0047] The following components are taken in percentage by weight: 25wt% HDPE resin, selected from CH2802 resin raw material; 7.5wt% anti-scratch enhancer, prepared in this embodiment; 2.6wt% compatibilizer, selected from TY-1053H HDPE-g-MAH resin raw material; 1.5wt% lubricant, selected from industrial grade calcium stearate and erucamide in a weight ratio of 2:1; 0.13wt% antioxidant, selected from antioxidant 1010 and antioxidant 168 in an equal weight ratio; the remainder is LLDPE resin, selected from LL103AA resin raw material;
[0048] The above raw materials were mixed in a high-speed mixer, and the mixture was melt-extruded by a twin-screw extruder. The temperature of the plasticizing zone was set at 200°C. The melt was extruded onto the surface of the aluminum substrate through a dividing die head and sent to a roller press. The pressure was controlled at 1.2±0.1MPa for hot pressing and compounding. The mixture was then sent to a tunnel oven and the temperature was controlled at 100°C for homogenization heat treatment for 30 minutes. Finally, the mixture was spray-cooled to form a PE plastic sealing layer on the surface of the aluminum substrate to obtain a scratch-resistant PE composite board.
[0049] Example 4, preparation of scratch-resistant PE composite board, the specific implementation process is as follows:
[0050] (1) Synthesis of scratch-resistant PE composite board
[0051] Step A1: Dimethyl difluoromalonate, diethylenetriamine and anhydrous toluene were pre-mixed, and dry nitrogen was introduced for protection. Trimethylaluminum was added and mixed, and the mixture was heated to 95°C with stirring and reflux for 4 hours. Then, n-butylamine was added and the reaction was continued for 0.7 hours. The dosage ratio of dimethyl difluoromalonate, diethylenetriamine, n-butylamine, trimethylaluminum and anhydrous toluene was 0.1 mol: 0.1 mol: 60 mmol: 0.18 g: 100 mL. After the reaction was completed, the toluene was removed by rotary evaporation to obtain intermediate 1.
[0052] Step A2: Premix the intermediate 1, 6-bromohexanol, and dimethylformamide, add potassium carbonate, and heat to 65°C with stirring for 7 hours. The ratio of the intermediate 1, 6-bromohexanol, potassium carbonate, and dimethylformamide is 50 g:0.18 mol:3.5 g:150 mL. After the reaction is completed and cooled, deionized water is added to wash, the aqueous phase is separated by centrifugation, and vacuum dried to obtain intermediate 2.
[0053] Step A3: Pre-mix the intermediate 2, triethylamine, and acetone, cool the mixture in an ice-water bath and control the temperature to be no higher than 10°C, introduce dry nitrogen for protection, slowly add tributylchlorosilane, and stir the mixture for 2 hours. Return the mixture to room temperature and continue stirring the mixture for 4 hours. The ratio of the intermediate 2, tributylchlorosilane, triethylamine, and acetone is 50 g:0.14 mol:18 mL:220 mL. After the reaction is completed, remove the acetone by rotary evaporation, then add saturated sodium bicarbonate solution for washing, separate the aqueous phase, and vacuum dry to obtain an anti-scratch strengthener.
[0054] (2) Preparation of composite panels
[0055] The following components are taken in percentage by weight: 23wt% HDPE resin, selected from CH2802 resin raw material; 8.8wt% anti-scratch enhancer, prepared in this embodiment; 2.4wt% compatibilizer, selected from TY-1053H HDPE-g-MAH resin raw material; 1.4wt% lubricant, selected from industrial grade calcium stearate and erucamide in a weight ratio of 2:1; 0.12wt% antioxidant, selected from antioxidant 1010 and antioxidant 168 in an equal weight ratio; the remainder is LLDPE resin, selected from LL103AA resin raw material;
[0056] The above raw materials were mixed in a high-speed mixer, and the mixture was melt-extruded by a twin-screw extruder. The temperature of the plasticizing zone was set at 200°C. The melt was extruded onto the surface of the aluminum substrate through a dividing die head and sent to a roller press. The pressure was controlled at 1.2±0.1MPa for hot pressing and compounding. The mixture was then sent to a tunnel oven and the temperature was controlled at 100°C for homogenization heat treatment for 30 minutes. Finally, the mixture was spray-cooled to form a PE plastic sealing layer on the surface of the aluminum substrate to obtain a scratch-resistant PE composite board.
[0057] In Comparative Example 1, referring to the implementation process of Example 4, an equal amount of the anti-scratch enhancer was replaced with commercially available coupled silica powder with a particle size of about 2 μm, and the rest of the implementation process was exactly the same.
[0058] Comparative Example 2, referring to the implementation process of Example 4, the anti-scratch strengthener was replaced with RF-901 fluorosilicone resin in equal amount, and the rest of the implementation process was exactly the same.
[0059] In order to facilitate the detection of the protective performance of the PE plastic sealing layer on the composite board, the mixture melt in the above implementation process was extruded into a mold and molded into a sample using the same process. The transmittance test was carried out according to the ASTM D1003-21 standard; the friction coefficient test was carried out according to the ISO 8295:2005 standard; the scratch test was carried out according to the ISO 1518-1-2019 standard; and the impact strength test was carried out according to the ISO 179-1-2023 standard. The specific test results are shown in Table 1:
[0060] Table 1
[0061] Transmittance / % Friction coefficient Visible scratch load / N 10N scratch width / μm Example 1 86.4 0.882 8.5 20 Example 2 85.7 0.904 7.9 17 Example 3 82.9 0.839 8.2 14 Example 4 84.1 0.812 8.9 12 Comparative Example 1 60.5 0.115 6.6 37 Comparative Example 2 84.6 0.793 5.2 54
[0062] It can be seen from the test data in Table 1 that the visible scratch load of the PE plastic sealing layer obtained in the embodiment reaches about 8N, the scratch width of 10N is no more than 20μm, the scratch is not easy to penetrate and expand, and it has good scratch resistance. The transmittance is maintained at more than 80%, and it has good transparency and aesthetics.
[0063] Throughout the specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in similar ways. As long as they do not deviate from the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.
Claims
1. A scratch-resistant PE composite board, consisting of a substrate and a PE plastic sealing layer, characterized in that: The components of the PE plastic sealing layer are: 18-25wt% of HDPE resin, 7.5-11wt% of anti-scratch enhancer, 1.9-2.6wt% of compatibilizer, 1.2-1.5wt% of lubricant and 0.1-0.13wt% of antioxidant, and the balance is LLDPE resin; The anti-scratch strengthener is prepared by the following method: Step A1: Dimethyl fluoromalonate, diethylenetriamine, and anhydrous toluene were premixed, and dry nitrogen was introduced. Trimethylaluminum was added and mixed thoroughly. The mixture was heated to 80-100°C and stirred under reflux for 3-4 hours. Then, n-butylamine was added and the reaction was continued for 0.5-0.7 hours to prepare Intermediate 1. Step A2: Premix the intermediate 1, 6-bromohexanol, and dimethylformamide, add potassium carbonate, and heat to 60-70°C, stirring and reacting for 5.5-7 hours to prepare the intermediate 2; Step A3: Premix the intermediate 2, triethylamine, and acetone, cool the mixture to a temperature not exceeding 10°C, introduce dry nitrogen gas for protection, slowly add tributylchlorosilane, and stir the mixture for 1.5-2 hours. Return the mixture to room temperature and continue stirring the mixture for 3-4 hours to prepare an anti-scratch strengthening agent.
2. The scratch-resistant PE composite board according to claim 1, characterized in that: The dimethyl fluoromalonate is one of dimethyl 2-fluoromalonate and dimethyl difluoromalonate.
3. The scratch-resistant PE composite board according to claim 2, characterized in that: The usage ratio of dimethyl fluoromalonate, diethylenetriamine, n-butylamine, trimethylaluminum and anhydrous toluene is 0.1 mol: 0.1 mol: 40-60 mmol: 0.1-0.18 g: 85-100 mL.
4. The scratch-resistant PE composite board according to claim 3, characterized in that: The usage ratio of the intermediate 1, 6-bromohexanol, potassium carbonate and dimethylformamide is 50 g: 0.14-0.18 mol: 2.5-3.5 g: 120-150 mL.
5. The scratch-resistant PE composite board according to claim 4, characterized in that: The usage ratio of intermediate 2, tributylchlorosilane, triethylamine and acetone is 50 g: 0.12-0.15 mol: 15-20 mL: 180-240 mL.
6. The scratch-resistant PE composite board according to claim 1, characterized in that: The compatibilizer is HDPE-g-MAH resin.
7. The scratch-resistant PE composite board according to claim 1, characterized in that: The lubricant is a compound of calcium stearate and erucamide.
8. A method for preparing a scratch-resistant PE composite board according to any one of claims 1 to 7, characterized in that: Specifically, the raw materials of each component are mixed evenly, melt-extruded onto the surface of the substrate, and then hot-pressed, homogenized, heat-treated and cooled to form a PE plastic sealing layer on the surface of the substrate to obtain a scratch-resistant PE composite board.
Citation Information
Patent Citations
Glue breaking and scratch resistant paint surface protective membrane and preparation method thereof
CN104694035A
Cracking-resistant and heat-resistant optical cable material and preparation method thereof
CN105924744A